Synthesis, characterization, and antibacterial activity of anion-depended Cu(II)-Niacinamide complexes - Nadia Cikita Handayani; Rio Risandiansyah; Anna Safitri; Yudi Purnomo; Yuniar Ponco Prananto (Kuwait Journal of Science)
This study aims to prepare different types of Cu(II)-niacinamide complexes by layered solution method from various source of Cu(II) salts (sulphate, nitrate, chloride, and acetate) and in various M(II):niacinamide molar ratio (1:2, 1:4, and 1:6). The complexes were characterized by infrared spectroscopy, melting point test, powder-XRD, anion qualitative test, and scanning electron microscopy. The antibacterial activities of those complexes were also explored. Experimental data reveals that anion of the Cu(II) affects the crystallization of Cu(II)-niacinamide complex, in which various shape and type of solid products were formed, namely light blue hair-like crystals (sulphate), dark green block crystals (acetate), and turquoise sword-like microcrystalline (chloride). These three anions act either as free ion in the crystal lattice (chloride) or as ligand (sulphate and acetate). Based on the characterization, the crystals obtained from the sulphate, chloride, and acetate reactions were predicted to be complexes of [Cu(L)x(SO4)], [Cu(L)x]Cl2, and [Cu2(L)4(CH3COO)2], respectively, where L ​= ​niacinamide. Furthermore, antibacterial test of the three complexes towards E. coli and S. aureus shows that the complexes have better activity than that of the free niacinamide.